2011
DOI: 10.1038/hdy.2011.81
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of differentiation between traits and their underlying genes in response to divergent selection

Abstract: We dissected the relationship between genetic differentiation (Q ST ) for a trait and its underlying genes (G STq , differentiation for a quantitative locus) in an evolutionary context, with the aim of identifying the conditions in which these two measurements are decoupled. We used two parameters (y B and y W ) scaling the contributions of inter-and intrapopulation allelic covariation between genes controlling the trait of interest. We monitored the changes in y B and y W , Q ST and G STq over successive gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 50 publications
(49 reference statements)
4
108
1
1
Order By: Relevance
“…Noticeably, this local adaptation did not completely erode within-population genetic variation of adaptive traits (Mimura and Aitken 2007;Alberto et al 2013). The long-term maintenance of evolvability also depends on the genetic architecture of the traits under selection, and in the case of polygenic inheritance, Kremer and Le Corre (2012) showed that evolutionary changes first result from the selection of the fittest combinations of gene alleles before it reduces the allelic diversity at individual gene loci.…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, this local adaptation did not completely erode within-population genetic variation of adaptive traits (Mimura and Aitken 2007;Alberto et al 2013). The long-term maintenance of evolvability also depends on the genetic architecture of the traits under selection, and in the case of polygenic inheritance, Kremer and Le Corre (2012) showed that evolutionary changes first result from the selection of the fittest combinations of gene alleles before it reduces the allelic diversity at individual gene loci.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we assigned a range of values for those parameters that we purposely investigated: pollen migration models, level of divergent selection, intensity of stabilizing selection, degree of assortative mating and directions of environmental and genetic gradients ( Table 2). The range of values have been investigated through sensitivity analysis in earlier investigations using Metapop (Le Corre and Kremer, 2003;Kremer and Le Corre, 2011;Soularue and Kremer, 2012). In total, we considered 42 scenarios and ran 30 independent replicates over 1000 generations for each of them.…”
Section: Simulation Settingsmentioning
confidence: 99%
“…Yet, the majority of trait associated SNPs were not F ST outliers (S2 Table) and appeared to be unresponsive to selection for different climatic conditions, especially for phenology traits such as bud set, leaf drop or growth period. A previous simulation study suggested that differentiation in candidate loci is limited for complex traits in forest trees (i.e., their F ST values are similar to neutral values), despite their strong adaptive divergence among local populations (high Q ST ), due to large population sizes and high levels of gene flow [52]. Thus, highly polygenic adaptation (as observed in complex genetic traits) will not show sufficient allele frequency differentiation such that climatic clines in SNPs of candidate genes can be exhaustively detected.…”
Section: Selectively Non-neutral Genetic Variants Underlying Traits Amentioning
confidence: 99%